Being Brains : Making the Cerebral Subject. - Vidal, Fernando (Forms of Living Ser., 2017)
Sketches the history of the belief that human beings are essentially their brains, and documents and critically discusses its contemporary forms across a range of contexts, including mental health, the human sciences, and literature and film.